The Effectiveness of Telegram as A Medium of Learning During the Pandemic in Indonesian Subjects in SMPN 6 Karawang Barat School Year 2019-2020 - Widati Marda; Heris Hendriana (JLER (Journal of Language Education Research), 2023)
The COVID-19 pandemic has brought major changes in the world of education. Learning activity that was originally done face-to-face became distance learning, so it needed interesting and easy-to-use learning media for teachers and students. One medium that is easy to apply and has many advantages is telegram because it has advantages among others. It is cloud-based, able to send files with large capacity, and easy to use. The number of group members reaches 200,000. It has many features, and can be accessed from several devices at once. There are many learning media that can be used for online learning. This study aims to determine the effectiveness of telegram as a learning medium and as an online evaluation tool. In addition, it is also done to determine student's responses to the telegram application used in learning. This study used a descriptive qualitative approach with a sample of 99 students at SMPN 6 Karawang Barat. The instruments used are in the form of surveys, interviews, and documentation; the results showed that 91 students liked telegram as a medium of learning. In addition, telegram was effectively used for media and learning assessment tools both for the assessment of knowledge, attitudes, and skills.